Percutaneous mechanical circulatory support from the collaborative multicenter Mechanical Unusual Support in TAVI (MUST) Registry. Issue 6 (7th May 2021) - Orvin, Katia; Perl, Leor; Landes, Uri; Dvir, Danny; Webb, John George; Stelzmüller, Marie‐Elisabeth; Wisser, Wilfried; Nazif, Tamim Michael; George, Isaac; Miura, Mizuki; Taramasso, Maurizio; Pilgrim, Thomas; et al.
Abstract: Objectives: To evaluate the use and outcomes of percutaneous mechanical circulatory support (pMCS) utilized during transcatheter aortic valve implantation (TAVI) from high‐volume centers. Methods and results: Our international multicenter registry including 13 high‐volume TAVI centers with 87 patients (76.5 ± 11.8 years, 63.2% men) who underwent TAVI for severe aortic stenosis and required pMCS (75.9% VA‐ECMO, 19.5% Impella CP, 4.6% TandemHeart) during the procedure (prior to TAVI 39.1%, emergent rescue 50.6%, following TAVI 10.3%). The procedures were considered high‐risk, with 50.6% having severe left ventricular dysfunction, 24.1% biventricular dysfunction, and 32.2% severe pulmonary hypertension. In‐hospital and 1‐year mortality were 27.5% and 49.4%, respectively. Patients with prophylactic hemodynamic support had lower periprocedural mortality compared to patients with rescue insertion of pMCS (log rank = 0.013) and patients who did not undergo cardiopulmonary resuscitation during the TAVI procedure had better short and long term survival (log rank <0.001 and 0.015, respectively). Conclusions: Given the overall survival rate and low frequency of pMCS‐related complications, our study results support the use of pMCS prophylactically or during the course of TAVI (bailout) in order to improve clinical outcomes in high‐risk procedures or in case of acute life‐threatening hemodynamic collapse.